Transport processes in macroscopically disordered media : from mean field theory to percolation /: from mean field theory to percolation. (2016) - Snarskii, Andrei A; Bezsudnov, Igor V; Sevryukov, Vladimir A; Morozovskiy, Alexander; Malinsky, Joseph
No abstract available